2004
DOI: 10.1002/adma.200306040
|View full text |Cite
|
Sign up to set email alerts
|

Microcontact Printing of CdS/Dendrimer Nanocomposite Patterns on Silicon Wafers

Abstract: Micrometer‐scale patterns of blue photoluminescing CdS nanoparticles can be produced by microcontact printing on a hydroxyl‐terminated silicon wafer surface (see Figure). The CdS nanoparticles were synthesized with amine‐terminated generation eight dendrimers as stabilizers. The resulting CdS/dendrimer composite is directly printable due to hydrogen bonds between dendrimer and surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Dendrimer-stabilized nanoparticles show effective adsorption on surfaces by multiple hydrogen bonds. [34] Here, the roughness of the surface might play a more important role as we could see that more particle aggregates adsorbed on the edges of the Au pattern and on the rough Au pattern. The formation of larger aggregates suggested that the interaction between the nanoparticles was stronger than that between the nanoparticles and the surface.…”
Section: Selective Adsorption Of Nanoparticles On a Patterned Surfacementioning
confidence: 97%
“…Dendrimer-stabilized nanoparticles show effective adsorption on surfaces by multiple hydrogen bonds. [34] Here, the roughness of the surface might play a more important role as we could see that more particle aggregates adsorbed on the edges of the Au pattern and on the rough Au pattern. The formation of larger aggregates suggested that the interaction between the nanoparticles was stronger than that between the nanoparticles and the surface.…”
Section: Selective Adsorption Of Nanoparticles On a Patterned Surfacementioning
confidence: 97%
“…7F), [107±109] as well as for alkylsiloxanes on hydroxyl-terminated substrates, [110] and alkylphosphonic acids on aluminum oxide. [111] Other interesting examples include the direct printing of chemical species such as catalysts or catalytic precursors, [112] colloidal particles, [113] dendrimers, [114] organic reactants, [115] conventional polymers, [116] lipid bilayers, [117] and proteins. [118] In addition to liquid-based inks, a thin, evaporated film of metal (e.g., gold or aluminum) can also be readily transferred onto the surface of a substrate using a variant of this technique termed nanotransfer printing (nTP).…”
Section: Printing With An Elastomeric Stampmentioning
confidence: 99%
“…The surfaces (0.5 0.5cm 2 size) were ultrasonically cleaned in acetone (99.5%, Merck) for 30 seconds and flushed by copious Milli Q water (18 M .cm [13]. The hydroxyl terminated silicon (Si-OH) was incubated in the 0.1mg/mL DCC and 0.12mg/mL shortened nanotubes (8 hours cutting in mixed acid, RFP-SWCNT, Carbon Solutions, Inc. USA)/DMSO ( 99.9%, Spectrophotometric Grade, SigmaAldrich) solution for different reaction times to make carbon nanotubes directly attached to silicon surfaces.…”
Section: Expermimentalmentioning
confidence: 99%